2020
DOI: 10.1080/09535314.2020.1804330
|View full text |Cite
|
Sign up to set email alerts
|

Weaponized trade policy: the impact of US tariffs on the European automobile sector

Abstract: With trade tensions running high, the Trump Administration is considering new tariffs on imported automobiles, and the main target would be the European Union, traditionally America's closest ally. In this paper we combine disaggregated models to estimate the impact of these tariffs worldwide, and especially on Spain. First, a trade-policy simulation model computes the potential effects worldwide. Then we plug these into the World Input-Output Database, obtaining the inter-sectoral effects of the tariffs on Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The literature on transmission of trade shocks is somewhat mixed. While Korea [20] other South East Asian countries [13,21] and Europe [22][23][24] have experienced adverse effects from trade shocks, some Asian cases have reported minor impacts from US-China trade distortion. Aslam [25] concluded that trade tensions could harm indirect exports from Southeast Asian countries (ASEAN) to the US, although identifying a possible scenario where ASEAN countries might send substitute products for the Chinese exports to the US.…”
Section: Introductionmentioning
confidence: 99%
“…The literature on transmission of trade shocks is somewhat mixed. While Korea [20] other South East Asian countries [13,21] and Europe [22][23][24] have experienced adverse effects from trade shocks, some Asian cases have reported minor impacts from US-China trade distortion. Aslam [25] concluded that trade tensions could harm indirect exports from Southeast Asian countries (ASEAN) to the US, although identifying a possible scenario where ASEAN countries might send substitute products for the Chinese exports to the US.…”
Section: Introductionmentioning
confidence: 99%